Placing Women's Voices in the Centre of a Strategy for the Prevention of Child Sexual Abuse: Speaking from Our Strengths - MacQuarrie, Colleen; Robinson, Kelly E. (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
The premise for this paper is both basic and profound: survivors of child sexual abuse have the knowledge, experience, and perspective to lead in the efforts to stop it. It describes a draft strategy to prevent child sexual abuse, placing survivors at the core of the plan, that was generated at a two day gathering for female survivors of childhood sexual abuse.